Park May Berhad Confronting The Competitive Public Transportation Industry In Malaysia - Chia, Yaroni Ching Ling (2003)
A case study of Park May Berhad regarding its confrontation of the competitive public transportation industry in Malaysia. The internal and external environment of the organisation is explored and this also including understanding its major competitors.